Cluster containment strategy: addressing Zika virus outbreak in Rajasthan, India. Issue 5 (September 2019) - Singh, Ruchi; Gupta, Veenu; Malhotra, Bharti; Singh, Sujeet; Ravindran, P; Meena, Deepa; Gupta, Jyoti; Mathur, VK; Mathur, Ravi Prakash; Singh, Sunil; Sharma, Pratibha; Sharma, Himanshu; et al.
Abstract : India is at risk of Zika virus transmission due to high prevalence of its vector Aedes aegypti . Rajasthan, a state in the north-west region of India, has also high prevalence of Aedes mosquito. First laboratory confirmed case of Zika virus disease in Rajasthan was reported on 21 September 2018 in Jaipur. The Government of Rajasthan quickly implemented a containment strategy to contain the outbreak and prevent further spread of this disease. Strategy included active human and mosquito surveillance, laboratory testing and sequencing of the virus, integrated vector control measures, intersectoral coordination, risk communication and social mobilisation, all in a predefined geographic area around the epicentre. Timely action with appropriate coordination at all levels with multiple stakeholders contained the outbreak successfully. In all, 159 confirmed cases were reported from in and around the 3 km containment zone in Shastri Nagar area of Jaipur City and routine surveillance. Following this, a specially developed laboratory-based surveillance strategy was put in place to ensure that the disease does not spread beyond the containment zone. No fresh case was reported subsequently within or beyond the containment zone.